What Is Climate X? An Essay on Joel Wainwright and Geoff Mann's Climate Leviathan: A Political Theory of Our Planetary Future. Issue 4 (1st October 2020) - Foran, John
Abstract : This essay critically assesses Joel Wainwright and Geoff Mann's Climate Leviathan, arguing that its excellent framework for thinking about the various possible futures of global climate governance provides valuable strategic and theoretical perspectives for the global climate-justice movement to better fight for its preferred outcome, which the authors call Climate X and which this essay terms, somewhat interchangeably, climate democracy, radical climate justice, or intersectional ecosocialism.